KISARAN INANG ISOLAT Colletotrichum gloeosporiodes ASAL MANGGA PADA BEBERAPA PASCAPANEN BUAH - Evan Purnama Ramdan; Inti Mulyo Arti; Ummu Kalsum; Putri Irene Kanny (Universitas Gunadarma, 2022)
Colletotrichum gloesporiodes is one of the species of Colletotrichum that causes anthracnose on various fruits both in the field and postharvest. C. gloesporiodes is a cosmopolitan pathogen so it is important to know which fruits can be infected as a basis for prevention. This study aimed to determine the host range and virulence level of C. gloesporiodes in several postharvest fruits. The research was conducted at the Agrotechnology Intermediate Laboratory, Gunadarma University from March 2022 to April 2022. This study used a completely randomized design consisting of 4 types of fruit (mango, chili, papaya, and tomato) as treatment. Each treatment consisted of 4 units and then repeated 3 times so that there were a total of 48 experimental units. C. gloesporiodes isolate was obtained from mango fruit with anthracnose symptoms. The isolates obtained were inoculated to tomatoes, chilies, papayas, and mangoes as controls. Anthracnose symptoms and lesin diameter were observed at 7 days after inoculation. The diameter of the lesin was measured to determine the level of virulence. The results showed that C. gloesporiodes was able to colonize and infect chilies, papayas, and mangoes as hosts, but there was no inoculated to tomatoes. The ability to colonize and infect is indicated by symptoms in the form of yellow to black spots, sunken, and watery. The virulence category showed different levels in each fruit with a range from very low to moderate. The conclusions obtained from this study were that C. gloesporiodes was able to infect chilies and papayas with different levels of virulence.